USING THE SIMPLEX METHOD TO IMPROVE SALES VOLUME IN E-COMMERCE MARKETS. - Abdelgadir, Somaia Osman Mohamed; Ahmed, Ahmed Osman Ibrahim (Scientific Culture, 2026)
This study aims to identify the role that one of the operations research methods (the simplex method) can play in overcoming the challenges facing e-commerce channels, which strive to achieve maximum sales volume. This mechanism is based on the principle of linear programming, where an initial solution is formulated to address the problem of maximizing profits or minimizing costs. The solution is then refined using the simplex method or the major (M) method to ultimately reach the maximum production volume, which in turn maximizes profit value. The study showed that sales in e-commerce markets result from the interaction between price levels, promotional intensity, consumer behavior, and product assortment decisions. The study also highlighted the importance of sensitivity analysis, given its ability to measure variables without affecting the optimal production quantity. The primary objective is to provide decision-makers with the flexibility to deal with changing market conditions, such as price volatility, and to ensure the soundness and quality of the decisions made. The study also highlighted the importance of determining the shadow price, a concept used to identify the opportunity cost or the expected increase in profits from acquiring an additional unit of a scarce resource. This is particularly crucial given the intense competition in the e-commerce world. The study recommended designing effective marketing and promotional strategies using quantitative analysis tools such as the simplex method and its related techniques, like sensitivity analysis or shadow pricing. These tools help in dealing with the rapid and unexpected changes in markets, especially in the world of e-commerce and digital marketing.